Global Existence of Weak Solutions to a Fractional Model in Magnetoelastic Interactions - Idriss Ellahiani; EL-Hassan Essoufi; Mouhcine Tilioua (Abstract and Applied Analysis)
The paper deals with global existence of weak solutions to a one-dimensional mathematical model describing magnetoelastic interactions. The model is described by a fractional Landau-Lifshitz-Gilbert equation for the magnetization field coupled to an evolution equation for the displacement. We prove global existence by using Faedo-Galerkin/penalty method. Some commutator estimates are used to prove the convergence of nonlinear terms.